Alianza de saberes del cuidado popular y cuidado profesional en la promoción de salud del lactante - Cardoza Sernaqué, Manuel Antonio (2022)
Con ferencia en 2nd LACCEI International Multiconference on Entrepreneurship, Innovation and Regional Development - LEIRD 2022: “Exponential Technologiesand Global Challenges: Moving toward a new culture of entrepreneurship and innovation for sustainable”, Virtual Edition